EVALUASI KEBIJAKAN PENERTIBAN TERNAK DI KECAMATAN PARIGI KABUPATEN PARIGI MOUTONG - Ikbal, Mohamad (Katalogis, 2015)
Curbing livestock is an attempt to make the control of the maintenance of livestock are not grounded and live roam in public places. The aim of research to uncover why the policy of curbing livestock in the district Parigi Parigi district Moutong not implemented effectively and efficiently?. This type of research is used qualitative selection techniques and the number of informants purposively selected informants 8 people. The theory used evaluation model William N Dunn with aspects: effectiveness, efficiency, adequacy, grading, responsiveness and accuracy. The results showed that the evaluation policy Animal Control in Sub Parigi Parigi district Moutong not deliver maximum results for its implementation has not been effective due to a lack of socialization and animal enforcement activities since the issuance of the regulations in 2005; inefficient due to the lack of operational funds allocated adequate control of cattle in each of the implementing agencies; but from the aspect of responsiveness and accuracy of that where regulation is appropriate and highly expected by the community because of the benefits that can be perceived by the public.